gamma-L-glutamyl-5-hydroxy-L-tryptophan, but not gamma-L-glutamyl-L-tryptophan, causes sodium retention in normal man - Li Kam Wa, T C; Freestone, S; Samson, R R; Johnson, N R; Lee, M R (British journal of clinical pharmacology, 1996)
1. This randomized, placebo-controlled, cross-over study compared the relative effectiveness of gamma-L-glutamyl-5-hydroxy-L-tryptophan (glu-5-HTP) and gamma-L-glutamyl-L-tryptophan (glu-TRP) in terms of their ability to act as substrates for renal 5-hydroxytryptamine (5-HT) synthesis and their actions on urinary sodium excretion. 2. Urinary excretion of 5-HT and sodium were determined before, during and after 1 h intravenous infusion of an equimolar amount (45 nmol kg-1 min-1) of glu-5-HTP or glu-TRP or placebo in nine healthy male subjects. 3. Cumulative urinary 5-HT excretion over the 4 h after the start of glu-5-HTP infusion was 350-fold greater than that after placebo, and this was associated with a reduction in the urinary excretion of sodium. 4. In contrast, the urinary excretion values of 5-HT and sodium after administration of glu-TRP were not significantly different from those observed on the placebo day. 5. The marked increase in urinary 5-HT excretion and the retention of sodium after administration of glu-5-HTP have been demonstrated in previous studies and result from increased intrarenal generation of 5-HT. The absence of a rise in urinary excretion of 5-HT after glu-TRP infusion suggests that there was no significant conversion of this glutamyl compound to 5-HT within the kidney. As a result, there was no effect on urinary sodium excretion.